Population growth, the natural rate of interest, and inflation - Sebastian Weiske (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2019)
Population growth rates have fallen considerably in most developed countries. An important question for monetary policy is whether this has led to a fall in the natural rate of interest. In representative agent models, the response of the natural rate to a fertility shock crucially depends on the preference parameter determining how households weight generations of different size. Estimating a medium-scale model of the US-economy featuring fertility shocks, I find that declining population growth has lowered both the natural rate and inflation by about 0.4 percentage points in recent decades.
Keywords: D64; D91; E31; E32; E52; J11; 330; inflation; business cycles; monetary policy; natural rate of interest; demographic transition